Controle da infecção fúngica pelos extratos de alho (Allium sativum L.) e modulação da atividade de macrófagos peritoneais em modelo murino de esporotricose - Burian, J. P. [UNESP]; Sacramento, L. V.S. [UNESP]; Carlos, I. Z. [UNESP] (FapUNIFESP (SciELO), 2017)
Garlic (Allium sativum L.) is grown all over the world as seasoning and medicinal vegetable since 3,000 BC. Allicin is the main component of garlic, being attributed to it the most of its biological activities, such as bactericidal, antifungal and antiviral actions. However, other compounds of garlic present antioxidant, hypocholesterolemic, vasodilator activities, protective action against different types of cancer, and immunomodulatory. Fungal infections are important causes of morbidity and mortality in people mainly in immunosuppressed ones. Sporothrix schenckii, the causing agent of Sporotrichosis (most common subcutaneous mycosis in Latin America), is dimorphic fungus, of saprophytic life in soil or plants, infecting people and animals mainly through skin injuries and bruises. The main of this work was to evaluate the influence of garlic consuming on immune modulation of healthy and infected Swiss mice in induced way by S. schenckii, since these animals functioning of peritoneal macrophages as well as the nitric oxide and cytokines’ production (IL-1β, IL-10 and IL-12) and to evaluate the antifungal potential of garlic with S. schenckii through minimum inhibitory concentration test and colony-forming units. The results showed that garlic offers antifungal potential with S. schenckii. The oral taking of garlic extracts influences the releasing of cytokines by macrophages, regular consuming shows anti-inflammatory effect, and its acute use may take to an inflammatory response. Mice that consumed garlic responded more effectively to fight against the infection.
Fungal infection control by garlic extracts (Allium sativum L.) and modulation of peritoneal macrophages activity in murine model of sporotrichosis
Keywords: Garlic; Interleukin; Macrophage; Sporothrix schenckii; Sporotrichosis